PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS POWTOON PADA MATERI VEGETABLES CUTTING UNTUK SISWA FASE E SMK NEGERI 1 BUDURAN - Talitha Jasmine Ardiningrum; Mein Kharnolis; Nugrahani Astuti; Ila Huda P. Dewi (STKIP Subang, 2026)
The teaching of vegetables cutting at SMK Negeri 1 Buduran has relied heavily on static materials such as printed modules and conventional slideshows, which are unable to present procedural visualizations dynamically. As a result, students struggle to distinguish the shapes, dimensions, and functions of various vegetable cutting techniques. This study aims to develop a Powtoon-based animated video learning media on vegetables cutting material, assess its feasibility based on expert evaluation, and examine students' responses to the developed media. The research employed a Research and Development (R&D) approach using the 4D development model (Define, Design, Develop, Disseminate), implemented up to the Develop stage. The research subjects consisted of 27 tenth-grade students from the Culinary Study Program at SMK Negeri 1 Buduran. Data were collected using media expert validation sheets, content expert validation sheets, and student response questionnaires based on a Likert scale. Media expert validation yielded a mean score of 3.75, while content expert validation obtained a mean score of 3.71, both categorized as Very Feasible. Student response reached an overall average of 94.75%, classified as Very Good. Therefore, the Powtoon-based learning media on vegetables cutting material was declared valid, feasible, and positively received by Phase E students of SMK Negeri 1 Buduran.